Ambient non-methane hydrocarbons and their contribution to ozone formation potential in a super coal chemical industry in China’s Energy Golden Triangle - Wang, Jinxiang; Ma, Jianmin; Liu, Panliang (Frontiers in Environmental Chemistry, 2022)
Ambient non-methane hydrocarbons (NMHCs) were investigated at Shenhua coal chemical industrial park (SH), and Baofeng coal chemical industrial park (BF) in Ningdong Energy and Chemical Industrial Base (NECIB) in China’s Energy Golden Triangle (EGT). Ambient air samples were collected using pre-evacuated 2-L electro-polished stainless steel canisters at SH and BF from 9:00 a.m. to 9:30 a.m. (UTC+8) from 22 to 31 December 2016. Fifty-seven NMHCs were analyzed using gas chromatography-mass selective detector/flame ionization detector. The average NMHCs mixing ratios were 49.05 ± 44.37 ppbv in SH, and 39.31 ± 18.77 ppbv in BF. Overall, alkanes took up the largest proportion (＞60%), followed by alkenes, acetylene, and aromatics. The propylene-equivalent (Prop-Equiv) concentration and the ozone formation potential (OFP) of NMHCs were calculated to estimate their chemical reactivities. Alkenes played a predominant role in NMHCs reactivity, among which propylene and ethylene were the largest contributors. OFP values show that alkenes and acetylene were the largest contributors (60%) to measured total NMHCs. Ethylene, propylene, m/p-xylene, n-butane, 1-butene, propane and acetylene were the major precursors in ground-level ozone formation in this region, which accounted for 66% and 62% of the total ozone formed by NMHCs at BF and SH, respectively. This study identified that industrial activities were the primary sources of NMHCs, confirmed by the high ratios of benzene to toluene (B/T = 2.23). Therefore, these organic pollutants should be monitored further based on their high toxicities.